2017
DOI: 10.4330/wjc.v9.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells: Exploring the pleiotropic effects of statins

Abstract: Statins have become a cornerstone of risk modification for ischaemic heart disease patients. A number of studies have shown that they are effective and safe. However studies have observed an early benefit in terms of a reduction in recurrent infarct and or death after a myocardial infarction, prior to any significant change in lipid profile. Therefore, pleiotropic mechanisms, other than lowering lipid profile alone, must account for this effect. One such proposed pleiotropic mechanism is the ability of statins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 200 publications
(217 reference statements)
0
21
0
Order By: Relevance
“…The results of this study clearly show that statin inhibits EBOV infection. Our results, combined with statins' known role in suppressing inflammation (74) and preserving endothelial integrity (75), pathways that are impaired in EVD, argue for a potential benefit of using statins as adjunctive therapy in patients with EVD. Ideally, the use of an antiviral that exhibits additional effects in combination with a statin has the potential both to block virus replication and to decrease the deleterious effects of inflammation on the host.…”
Section: Discussionmentioning
confidence: 66%
“…The results of this study clearly show that statin inhibits EBOV infection. Our results, combined with statins' known role in suppressing inflammation (74) and preserving endothelial integrity (75), pathways that are impaired in EVD, argue for a potential benefit of using statins as adjunctive therapy in patients with EVD. Ideally, the use of an antiviral that exhibits additional effects in combination with a statin has the potential both to block virus replication and to decrease the deleterious effects of inflammation on the host.…”
Section: Discussionmentioning
confidence: 66%
“…Statins are able to increase eNOS expression by inhibiting isoprenylation of Rho GTPase. Statins can also rapidly induce the phosphorylation and activation of eNOS via PI3K/Akt pathway (Gazzerro et al 2012, Sandhu et al 2017.…”
Section: The Pi3k/akt Pathway Angiogenesis and Nitric Oxide Pathwaymentioning
confidence: 99%
“…Statins have antioxidant pleiotropic effect, which can include indirect mechanism increasing NO bioavailability accounting for antioxidant properties. Secondly, statin therapy has also been shown to inhibit activation of NAD(P)H oxidase and ROS release and activation of catalase and thioredoxin ROS scavenging mechanisms (Sandhu et al 2017).…”
Section: The Pi3k/akt Pathway Rocks and Oxidative Stressmentioning
confidence: 99%
“…For example, it was demonstrated that diabetes mellitus [ 46 ], smoking [ 45 ], hypertension [ 47 ] and atherosclerosis [ 48 ] showed no effect on the quantity of EPCs. However, samples from patients treated with statins showed a correlation between quantity and/or functionality of EPCs with hyperlipidemia, hypertension, diabetes mellitus and atrial fibrillation [ 5 , 49 ]. The present results, which also demonstrated a lack of significant difference in the quantity of EPCs in relation to the presence or absence of screened vascular risk factors, are consistent with the previous findings.…”
Section: Discussionmentioning
confidence: 99%